Commitments by the biopharmaceutical industry to clinical trial transparency: the evolving environment. Issue 5 (21st March 2019) - Baronikova, Slavka; Purvis, Jim; Southam, Eric; Beeso, Julie; Panayi, Antonia; Winchester, Christopher
Abstract : Clinical trial sponsors have ethical obligations to register protocols, report study results and comply with applicable legal requirements. To evaluate public commitments to trial disclosure and rates of disclosure by members and non-members of the European Federation of Pharmaceutical Industries and Associations (EFPIA) and/or the Pharmaceutical Research and Manufacturers of America (PhRMA). Websites of the top 50 biopharmaceutical companies by 2015 sales were searched for statements relating to trial data disclosure. Disclosure of trial results completed by biopharmaceutical industry and non-industry sponsors of at least 30 trials (2006–2015) was assessed using TrialsTracker. Among the top 50 companies, 30 were EFPIA/PhRMA members and 20 were non-members, of which 26 and none, respectively, had a statement on their website committing to the disclosure of trials data. Of 29 377 trials in TrialsTracker, 9511 were industry sponsored (69 companies) and 19 866 were non-industry sponsored (254 institutions). The overall mean disclosure rate was 55%, with higher rates for industry (74%) than for non-industry sponsors (46%). Of the 30 companies within the top 50 with data in TrialsTracker, the mean disclosure rate was 76% (77% for EFPIA/PhRMA members [n=25] vs 67% for non-members [n=5]). Most of the top 50 biopharmaceutical companies have publicly committed to the disclosure of trial data. Industry sponsors have responded to the ethical and legal demands of trial disclosure by disclosing three quarters of their trials compared with less than half for non-industry sponsors. Further improvements in clinical trial disclosure are needed.